Passionate and Pious: Religious Media and Black Women's Sexuality - Moultrie, Monique Nicole (Duke University Press, 2017)
Monique Moultrie explores the impact of faith-based sexual ministries on black women's sexual agency to trace how these women navigate sexuality, religious authority, and their spiritual walk with God